Mechanism and Kinetics Study in Homogenous Epoxidation of Vegetable Oil - Jalil, MJ; Yamin, AFM.; Azmi, IS; Jamaludin, SK.; Daud, ARM. (International Journal of Engineering and Technology, 2018)
Epoxide is an important chemical precursor for the production of alcohols, glycols and polymers like polyesters and epoxy resin. Commercial epoxides available in the market are mainly petroleum and animal based which are non-environmental friendly. The epoxidation of oleic acid was carried out by using in situ generated performic acid (HCOOOH) to produce epoxidized oleic acid. Performic acid was formed by mixing formic acid (as oxygen carrier) and hydrogen peroxide (as oxygen donor). Â The rate constant for epoxidation of oleic acid was found to be in the order of 4.203 x 10-5 mol-1 s-1 and activation energy is 7.58 kcal.mol-1. In addition, thermodynamic parameters such as enthalpy, entropy and free energy of activation of 6.83 kcal.mol-1, -57.36 cal.mol-1 K-1 and 22.96 kcal.mol-1 respectively.Â